Study The Effect Of Some Personality Variables On Communication Skills For Teachers Of Physical Education And Sports At The Secondary Level. - Zitoufi , : Abdelkader; Yousfi , Fethi (sports creativity, 2025)
The study aimed to try to identify the effect of each variable (gender - experience - academic qualification) on the communication skills of professors of physical education and sports in the secondary stage, where the researcher chose three initial hypotheses for this study that included three variables (gender, experience, academic qualification) and given the nature of the study The researcher relied on the descriptive approach, and the studied sample included 150 adolescents, who were chosen on the deliberate method of adolescents practicing physical education and sports at the secondary level. The study concluded that communication skills are affected by both the gender and experience variable while not affected by the educational qualification variable